Application of the new SEUMRE global optimisation tool in high efficiency EV/PHEV/EREV electric mode operations. (29th August 2011) - Younis, Adel; Zhou, Leon; Dong, Zuomin
Electric vehicles (EV/HEV/PHEV/EREV) draw mechanical power or regenerate electric power using multiple electric motors and generators (M/Gs). To achieve optimal vehicles electrical/mechanical energy conversion efficiency and to prolong the pure electric range of these vehicles, the energy conversion efficiency is to be maximised against powertrain component operation parameters using high fidelity model and simulation. However, the energy conversion efficiency model using vehicle powertrain component model and simulation is complex and computationally intensive. An efficient global optimisation tool is needed to produce the optimal efficiency look-up surface for real-time control system implementation, or to search for the optimal operation parameters in real time. In this work, a new two-mode-plus EREV design is used. The optimal vehicle energy conversion efficiency under various powertrain component operation parameters are obtained using three alternative global optimisation tools, GA, PSO, and SEUMRE. Application of SEUMRE allow refined and more accurate vehicle energy conversion efficiency map being created for the optimal operation of the EV/PHEV/EREV. Optimal vehicle control schemes can then be generated in determining the speed and torque of the M/Gs of the vehicle without violating their physical constraints and achieving the overall maximum efficiency of the hybrid powertrain system.